Recent advances in bioactive nanocrystal‐stabilized Pickering emulsions: Fabrication, characterization, and biological assessment. Issue 2 (22nd December 2022) - Yang, Dan; Feng, Yuqi; Yao, Xiaolin; Zhao, Baofu; Li, Dan; Liu, Ning; Fang, Yapeng; Midgley, Adam; Liu, Dechun; Katsuyoshi, Nishinari
Abstract: Numerous literatures have shown the advantages of Pickering emulsion (PE) for the delivery of bioactive ingredients in the fields of food, medicine, and cosmetics, among others. On this basis, the multi‐loading mode of bioactives (internal phase encapsulation and/or loading at the interface) in small molecular bioactives nanocrystal‐stabilized PE (BNC‐PE) enables them higher loading efficiencies, controlled release, and synergistic or superimposed effects. Therefore, BNC‐PE offers an efficacious delivery system. In this review, we briefly summarize BNC‐PE fabrication and characterization, with a focus on the processes of possible evolution and absorption of differentially applied BNC‐PE when interacting with the body. In addition, methods of monitoring changes and absorption of BNC‐PE in vivo, from the nanomaterial perspective, are also introduced. The purpose of this review is to provide an accessible and comprehensive methodology for the characterization and evaluation of BNC‐PE after formulation and preparation, especially in relation to biological assessment and detailed mechanisms throughout the absorption process of BNC‐PE in vivo.